Applied micro- and macro-reflective cycles in work-based learning and research: two advanced practice contexts. Issue 3 (3rd May 2020) - Fergusson, Lee; van der Laan, Luke; Ormsby, Gail; Azmy, Wade
ABSTRACT: In a previous study, we introduced principles of micro- and macro-reflective cycles as they relate to work-based learning and research. Micro-reflective cycles are common in the literature as these relate to critical reflection practiced by individuals in a variety of well-chronicled domains, including education, nursing, and business. Macro-reflective cycles, we posited, are less common and relate to reflective practice applied at the project, program, or research initiative level. We specifically showed how these cycles can occur within a work-based learning higher degree by research program, and we highlighted the interfaces between reflective cycles showing their centrality to work-based research, particularly when applied as part of a mixed methods design. In this paper, we explore two advanced practice contexts for micro- and macro-reflection made explicit through work-based learning reflection, one related to executive coaching in Singapore and Australia, and the other related to non-government community development in Cambodia, India, and Sri Lanka. We show how the researchers have reflected on these contexts by employing micro- and macro-reflection to explore work-based situations leading individuals, agencies, and companies to higher levels of performance and learning, and we discuss the research which supports each context.